ACT-13 DSP-0390, AN ORAL EMOPAMIL BINDING PROTEIN (EBP) INHIBITOR, IN PATIENTS WITH RECURRENT HIGH-GRADE GLIOMA: A FIRST-IN-HUMAN, PHASE 1 STUDY. (3rd December 2022) - Yoshiki, Arakawa; Reardon, David; Narita, Yoshitaka; Goldlust, Samuel; Anstass, George; McMullen, Dragana; Dow, Edward; Seki, Masataka; Furuta, Yudai; Song, Gregory; Colman, Howard
Abstract: Background: The brain's cells are fully dependent on their own de novo biosynthesis of cholesterol as the blood-brain barrier prevents its uptake from the circulation. In normal glial cells, proper regulation of cholesterol synthesis depends on its cell density and is turned off when the cell density exceeds a certain level. On the other hand, gliomas maintain high levels of cholesterol synthesis to support abnormal growth under any condition. Upregulation of cholesterol synthesis genes is associated with decreased survival in patients with glioblastoma (GBM). Therefore, gliomas are potentially sensitive to cholesterol synthesis inhibition. DSP-0390 is an investigational small molecule inhibitor of EBP, an enzyme in one of the last steps of cholesterol biosynthesis. By inhibiting de novo cholesterol synthesis, cytotoxicity can be induced more selectively against hyperproliferative GBM cells. DSP-0390 has shown significant antitumor activity in orthotopic xenograft GBM models (data on file). Methods: DSP-0390 will be evaluated in a phase 1 study in patients with recurrent high-grade glioma (NCT05023551). Key eligibility criteria: age ≥18 years; KPS score ≥70%; and adequate organ and hematologic function. Patients must not have multifocal disease, leptomeningeal metastasis, extracranial metastasis. In Dose Escalation, 21-30 patients with World Health Organization (WHO) grade III or IV malignant glioma who progressed after ≥1 prior therapy will be enrolled. Dose escalation will be guided by a Bayesian Logistic Regression Model until identification of the maximum tolerated dose or recommended dose for expansion. Dose Expansion will enroll approximately 20-40 patients with WHO grade IV GBM who progressed after primary therapy and have measurable disease. Study endpoints include safety (treatment-emergent adverse events [AEs], serious AEs, and dose-limiting toxicities), efficacy (6-month progression-free survival [PFS], objective response, PFS, duration of response, and 12-month overall survival), pharmacokinetics (PK), and pharmacodynamic biomarkers. This study is currently recruiting in the United States and Japan.